Amniotic membrane transplantation with and without limbal stem cell transplantation in chemical eye injury - Kafle, P A; Singh, S K; Sarkar, I; Surin, L (Nepalese Journal of Ophthalmology, 2015)
Introduction: Chemical burns of the eyes are one of the important causes of visual disability. Chemical burns particularly alkali burn may lead to gross limbal stem cell deficiency. Amniotic membrane transplantation with limbal graft is a good method for ocular surface reconstruction. Case: A 39 years male presented to Biratnagar Eye Hospital after 5 months of chemical injury with redness, pain, photophobia and gradual loss of vision. His visual acuity was counting fingers close to face in both eyes. Amniotic membrane transplantation alone was done in right eye while in left eye limbal stem cell allograft was combined with amniotic membrane transplantation. There was not much visual improvement in right eye while left eye improved significantly to 6/60.Conclusion: Limbal stem cell graft with amniotic membrane transplantation can be an effective method of restoring vision and reducing symptoms rather than amniotic membrane transplantation alone in cases with total limbal stem cell deficiency following chemical burn.